THERAPEUTIC EFFECT OF ABHAYA LAVANA WITH SHARAPUNKHA KWATHA IN THE MANAGEMENT OF CHOLELITHIASIS – CASE STUDY - Kumar, K P Sajith; Yaseen, Muhammed (International Research Journal of Ayurveda & Yoga, 2024)
Cholelithiasis is a worldwide medical condition, resulting from a combination of several factors like supersaturation of bile with cholesterol, accelerated nucleation of cholesterol monohydrate in bile, and bile stasis or delayed gallbladder emptying. Gallbladder stones present in one of three clinical stages: asymptomatic, symptomatic and with complications. The treatment options for asymptomatic range from no treatment to selective cholecystectomy. Laparoscopic cholecystectomy remains the default option for symptomatic cases. A definite non-invasive management is be a boon in asymptomatic and symptomatic uncomplicated gallstones. Abhaya Lavana is a strategic combination of Kshara & Lavana kalpana described in classical texts. Its indications point towards that this combination has a definite result in cholelithiasis and associated symptoms. Kwatha of Sharapunkha as anupana would definitely help to carry the drug to its site of action. To evaluate the effect of the treatment, A pre-post-test clinical study was conducted among the 13 participants. Clinical Intervention was done with 2g of Abhaya Lavana with 96ml of Sharapunkha Kwatha in the Middle of every Breakfast for 45 Days. Assessment of Subjective Parameters and Associated symptoms were done prior to the intervention and on 15th, 30th and 45th day. Pre and Post Assessment of Primary Objective - USG and Secondary objective - Lipid Profile were Conducted after Study. Safety of the Drug has been assessed by Pre and Post RFT and LFT. This study reveals that combined effect of Abhaya Lavana and Sharapunkha Kwatha is effective in Cholelithiasis and reducing associated symptoms.